Mediastinal hibernoma: a case report. Issue 9 (27th August 2004) - Baldi, A; Santini, M; Mellone, P; Esposito, V; Groeger, A M; Caputi, M; Baldi, F
Abstract : Hibernomas are rare benign tumours that arise most often in adults from the remnants of fetal brown adipose tissue. They usually affect muscle and subcutaneous tissue and are asymptomatic and slow growing. The distribution of this tumour follows the sites of persistence of brown fat. Out of more then 100 cases described in the word literature only three hybernomas were mediastinal. A recent clinicopathological study of 170 cases from the Armed Forces Institute of Pathology confirmed the exceptionality of the intrathoracic location. This report describes a very rare case of mediastinal hibernoma in a young man.